Estágios curriculares: autonomia inconteste e protagonismo discente revelados - Ramos, Inajara Vargas (Universidade do Vale do Rio dos Sinos, 2013)
This thesis by giving voice to student trainees from law and nursing courses of a community college in Rio Grande do Sul sought to unveil to meaning that the curricular internships, mandatory or not mandatory, assume in the academic and professional formation of these students and in the curriculum structure of their undergraduate courses. For that, two hundred and seventy two students and the coordination of both courses were heard, through in-depth structured and semi-structured interviews, following a qualitative/quantitative approach. The qualitative stage of ethnographic inspiration used the content analysis for the data treatment and the quantitative stage, characterized as descriptive conclusive research, field survey type, was analyzed statistically; as a research procedure, documental analysis was used too. The discussion of the dimensions experience, professionalization, theory/practice relation, formation, field and habitus, referenced in exponents such as Larrosa, Dewey, Dubar, Vázquez, Charlot and Bourdieu, amongst others, contributed greatly to unite the strings purposely forgotten by the analysis, threading the nets that brought the research to its acme. Thus, justifying the thesis, the study points that the curriculum of the undergraduate courses has much to gain by exploring the consequences and results of the curricular internships, mainly if the coordinations realize that the experiences lived by the trainees promote the student’s autonomy and independence. The university searches permanently to consolidate the interdisciplinary, the teaching-research-extension inseparability and the development of the student’s intellectual independency and doesn’t recognize the curricular internship, in its both modalities, as real and undisputed opportunities to achieve the objectives that justify the reason of its doing.
Keywords: Estágios curriculares; Protagonismo; Autonomia; Formação; Experiência; Curricular internships; Independence; Autonomy; Formation; Experience; ACCNPQ::Ciências Humanas::Educação